Where you left me : a memoir - Trulson, Jennifer Gardner (New York : Gallery Books, 2011)
This book is an account of the events of September 11, 2001, and their aftermath. Lucky, that is how the author would describe herself. She had a successful law career, met the love of her life in Doug, married him, had an apartment in New York City, a house in the Hamptons, two beautiful children, and was still madly in love after nearly seven years of marriage. She was living the kind of idyllic life that cliches are made of until Doug was killed in the attacks on the World Trade Center. This is an unlikely love story, a quintessentially New York story, the author's tribute to the city that gave her everything and proof that second chances are possible.
Keywords: Trulson, Jennifer Gardner; Trulson, Jennifer Gardner -- Marriage; Gardner, Douglas B., -- -2001.; September 11 Terrorist Attacks, 2001 -- Personal narratives; Husbands -- Death -- Case studies; Remarriage -- Case studies; New York (N.Y.) -- Biography